Advances in catalytic transesterification routes for biodiesel production using microalgae. (August 2022) - Lee, Jane Weng Yee; Chia, Wen Yi; Ong, Wee-Jun; Cheah, Wai Yan; Lim, Siew Shee; Chew, Kit Wayne
Graphical abstract: Highlights: Microalgae as an alternative feedstock for renewable biodiesel production. In-situ transesterification minimizes the loss of microalgal lipid. Ultrasonication and microwave heating assisted in microalgal lipid extraction. Nanocatalyst eliminates saponification thus enhancing process conversion yield. Solvents, moisture content, reaction time, and temperature affect biodiesel yield. Abstract: In the era of industrialization, the issues of greenhouse effect and depletion of unrenewable fossil fuels contributed to analyzing the potential of third-generation feedstock (microalgae) for biodiesel production owing to the cost-effectiveness, high lipid properties, and lesser carbon emission. In the conventional transesterification process, lipid and methanol are converted into alkyl esters and glycerol under the aid of a catalyst at 60 °C to 70 °C. However, in-situ transesterification is suggested over various process types due to the elimination of the costly and time-consuming drying and lipid extraction processes. The heating assisted methods including ultrasonic and microwave heating, aided in the lipid extraction have also been studied. It is found that heating-assisted methods can reduce the lipid extraction time and solvent usage. Apart from the heating assisted methods, operating factors affecting the alkyl esters conversion yield had been reviewed including solvent types, solvent/biomass ratio, reaction time, temperature, and moisture content. Also, various types of catalysts utilized in the process had been determined including homogenous catalyst, heterogeneous catalyst, and nanocatalyst. In short, this paper reviewed the advanced transesterification process for biodiesel production and the interaction of process parameters in optimizing the reaction conversion yield.